A Climatology of Cold Air Outbreaks and Their Impact on Air-Sea Heat Fluxes in the High-Latitude South Pacific - Papritz, Lukas; Pfahl, Stephan; Sodemann, Harald; Wernli, Heini; id_orcid:0 000-0001-9674-4837 (Journal of Climate, 2015)
ISSN:0894-8755 ISSN:1520-0442